1982
DOI: 10.1104/pp.70.4.1084
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Ice Nucleation: A Factor in Frost Injury to Plants

Abstract: Heterogeneous ice nuclei are necessary, and the common epiphytic ice nucleation active (INA) bacteria Pseudomonas syringae van Hall and Erwinia herbicola (Lihnis) Dye are sufficient to incite frost injury to sensitive plants at -5C. The ice nucleation activity of the bacteria occurs at the same temperatures at which frost injury to sensitive plants occurs in nature. Bacterial ice nucleation on leaves can be detected at about -2°C, whereas the leaves themselves, ie. without INA bacteria, contain nuclei active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
227
0
1

Year Published

1985
1985
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(234 citation statements)
references
References 12 publications
6
227
0
1
Order By: Relevance
“…9) into the model. For our comparison, we consider the experimental data gained in our measurements with LACIS as well as data from earlier experiments (Maki et al, 1974;Yankofsky et al, 1981;Lindow et al, 1982;Wood et al, 2002). Results are shown in Fig.…”
Section: Application Of the Nucleation Rate To Experimental Datamentioning
confidence: 98%
See 2 more Smart Citations
“…9) into the model. For our comparison, we consider the experimental data gained in our measurements with LACIS as well as data from earlier experiments (Maki et al, 1974;Yankofsky et al, 1981;Lindow et al, 1982;Wood et al, 2002). Results are shown in Fig.…”
Section: Application Of the Nucleation Rate To Experimental Datamentioning
confidence: 98%
“…However, Lindow et al (1982) directly reported frozen fractions. They analysed the freezing of P. syringae cells as function of temperature and cell concentration.…”
Section: Application Of the Nucleation Rate To Experimental Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Thus it would seem that in nature, plants will always supercool to some extent and it follows that eliminating INA bacterial cells from the plant tissue surfaces allows plants to protect themselves from freezing by enabling supercooling. This approach is being used in California to protect blossom in almond and peach orchards from spring radiation frosts (Lindow et al 1982) but has not been used systematically elsewhere. Fuller et al (2007) have demonstrated in vitro that the use of compounds that help shed surface water decreases the Figure 4.…”
Section: Utilizing the Infrared Camera In Cold Tolerance In Plantamentioning
confidence: 99%
“…Furthermore, for a given strain, the activity frequencies can be influenced by the host plant species. Lindow et al (1982) have shown that there were different activity frequencies between potato and tomato crops at -5°C. Moreover, some studies have shown that the variability of nucleating frequencies is a function of seasonal and diurnal changes for some bacterial populations (Hirano and Upper, 1989).…”
Section: Introductionmentioning
confidence: 99%